The Effects Of Supply Chain Management On Competitive Advantage: The Case Of Manufacturing Companies In Ethiopia - Mohammed Yassin Isho (International Journal of Business Studies, 2022)
Abstract Now a days firms are not only competing as autonomous units instead they entered in to an era of competing among different supply chains, leading them to work as a team in the form of network of business relationship. As competition becomes stiff, firms must be more involved in how their suppliers and customers conduct their businesses. To succeed in today’s challenging business environment, firms must be able to effectively integrate the internal function within a company and effectively link them with the external operations of supply chain members. Due attention should be given by firms to supply chain management practices as it has significant influence in enhancing SCM functions and ultimately performances. Accordingly, the objective of this study is to examine the practices and effect of supply-chain management on firms’ competitive advantage; and to look at the effect of inventory management on firms’ performance. Moreover, the study attempted to identify major challenges of supply-chain management in selected manufacturing firms in Ethiopia. To attain the objectives quantitative approach was employed. Moreover, a descriptive inquiry along with causal research design was used. Primary data were obtained from survey questionnaires. Large manufacturing firms; 2 textiles and 2 sugars were selected as samples using purposive sampling technique. In addition, 4 officials from each of the eight departments’ viz., General Managers, Purchasing managers, Technical managers, Operation managers, Quality managers, Transport managers, Sales and IT managers were selected from the four firms included in the study. Hence, a total of 128 respondents from each of the three studies were judgmentally selected. The collected data were analyzed using SPSS 20.0 version using descriptive statistics, Correlation analysis and multiple regressions analysis. Accordingly, based on the regression result it is revealed that the supply chain dimensions included in the study viz., customer relationship management, customer service management, level of information sharing, demand management process, environmental issues, and supplier relationship management were positively and significantly affect firms competitive advantage. Finally, it is suggested that manufacturing firms should create close relationship with customers to differentiate their products from competitors. Moreover, manufacturing firms are recommended to apply information technology like electronic data interchange within and among the supply chain umbrellas as a whole.